PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA YANG MENYENANGKAN UNTUK ANAK USIA DINI - Fatikhah Megar Panggalih; Muhammad Azka Maulana; Abdul Muiz Rouf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early childhood education (PAUD) in Indonesia still faces challenges, including low participation, varied accreditation status, and limited teacher competence in mathematics. Monotonous teaching methods and the absence of engaging modules hinder meaningful learning and reinforce the view that mathematics is difficult. This study aimed to develop play-based mathematics modules as practical guides for teachers. Using a simplified Borg and Gall model, the research covered five stages: data collection, product planning, initial development, expert validation, and revision. The modules were designed for three age groups (3–4, 4–5, and 5–6 years) with content aligned to NCTM standards. Validation results indicated feasibility ratings of 81% from content experts and 93% from media experts, both categorized as “highly feasible.” Practitioner interviews further confirmed the modules’ clarity, relevance, and appeal. Therefore, the modules are highly suitable as learning resources to support effective and enjoyable mathematics instruction in early childhood education.